Maple-assisted accelerated learning to enhance learning interest of senior high school students - W Ediningrum (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This research was motivated by the importance of learning interest of students.Learning interest of students is still low. In order that this problems can be solved, a learning model that can enhance learning interest of students is required. In this research, Maple-Assisted Accelerated Learning was selected. This study aims to analyze the enhancement learning interest of students. This research was a quasi-experimental with pretestposttest control group design. The population was students at tenth grade in one of senior high schools in Purwokerto, Central Java. The sample consisted of two classes which was selected by purposive sampling. This research used four instruments:, learning interest questionnaire, observation sheets, and interview guide. Data analyzed was done quantitatively. The data were analyzed by using Mann-Whitney U Test and Chi Squaren test. Based on the data analyze, it is found that: (1) the achievement of learning interest ability of students who received the Maple-Assisted Accelerated Learning is better than the achievement of students who received conventional learning; (2) the enhancement of learning interest of students who received the Maple-Assisted Accelerated Learning is better than the enhancement of students who received conventional learning.